Opportunities for Hospital-Based Telemedicine Development: A Systematic Review - Jayantika Sakina Ifnadera; Siti Soekiswati; Yusuf Alam Romadhon (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to examine the adoption, hospital integration, and revenue implications of telemedicine, with specific emphasis on Indonesia where hospital-based telemedicine services remain less developed than commercial platforms. The review focuses on identifying key drivers of user acceptance, organizational readiness, and financial outcomes to support strategic telemedicine development in hospitals.Methodology: A systematic review was conducted using a comprehensive search of open-access empirical studies published from 2020 to 2025. Twenty-six eligible articles were identified and analyzed. Data were synthesized thematically across three domains: factors influencing user adoption, hospital-level implementation processes, and the economic impact of telemedicine services. The review integrates both global and Indonesian evidence to provide a comparative perspective.Results: Findings show that perceived usefulness, trust, and digital readiness consistently shape patient and provider adoption of telemedicine. Successful hospital integration is supported by adequate infrastructure, clear governance, and alignment with clinical workflows. Several studies report cost-effectiveness and increased service utilization, indicating potential for enhanced hospital revenue, although economic evidence from Indonesian hospitals is still emerging.Applications/Originality/Value: This review offers practical insights for policymakers and hospital administrators planning long-term institutionalization of telemedicine. It is original in combining global and Indonesian contexts while emphasizing the financial sustainability of hospital-based telemedicine services.